Biocontroller Activity Macromycetes - Laguna, Aurora Castillo; Saldaña, Deyanira Rodriguez; Zambrano, Carlos Abed Martinez; Morales, Jose Emmanuel Colchero; Vargas-Álvarez, Dolores (European Journal of Applied Sciences, 2024)
Diseases caused by phytopathogens cause great damage in agricultural production and with it great economic losses. Today a wide variety of macromycetes are known capable of eliminating pests in a crop without having to use agrochemicals, which we know are harmful to the soil and the environment, however thousands of tons of agrochemicals are applied annually throughout the world Given the need to establish a control system that is more environmentally friendly, and given the need to mitigate this damage, various studies have shown that some macromycetes are a potential source of antifungal compounds that could be used to control these diseases. Therefore, the objective of this review is to collect information on macromycetes that present biocontroller activity, among which are the genera Xylaria, Agrocybe, Psilocybe, Stereum, Pycnoporus sanguineus, lentinus crinitus, Cordyceps, Hymenostilbe and Tolypocladium cylundrosporum on different phytopathogenic fungi.